IN SILICO GENE EXPRESSION ANALYSIS OF THE STRESS-RELATED NAC-A GENE SUBFAMILY TO DISSECT THEIR ROLE IN ABIOTIC STRESS TOLERANCE IN BREAD WHEAT (TRITICUM AESTIVUM L.) - Al-Sayaydeh , Rabea; Al-Habahbeh, Khaled; Akkeh, Zahera; Albdaiwi, Randa N. (Jordan Journal of Agricultural Sciences, 2021)
Wheat is a major staple crop that is largely affected by different abiotic stresses that include heat, drought, and salinity. The main objective of this study was to identify wheat NAC transcription factors that are related to the NAC-a subfamily, which is involved in mediating stress tolerance in different plant species. Furthermore, in silico gene expression analysis was conducted to detect differential changes in wheat NAC-a subfamily members in different organs, developmental stages, and under various abiotic stress. Herein, using phylogenetic analysis for 488 NAC transcription factors, 41 proteins were identified as wheat NAC-a subfamily members. In silico gene expression analysis found that NAC-related wheat transcription factors are expressed exclusively at the anthesis stage till dough development with high expression levels detected in flag leaves. The in-silico gene expression analysis identified SNAC1-related members, which had high expression levels under drought, cold, and heat stresses. The identified stress-induced wheat NAC-a subfamily members can be utilized in the future to develop climate-smart wheat cultivars with improved tolerance against abiotic stresses.